2021
DOI: 10.1111/cas.15053
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐binding protein SAMD4A inhibits breast tumor angiogenesis by modulating the balance of angiogenesis program

Abstract: Tumor‐induced angiogenesis is important for further progression of solid tumors. The initiation of tumor angiogenesis is dictated by a shift in the balance between proangiogenic and antiangiogenic gene expression programs. However, the potential mechanism controlling the expression of angiogenesis‐related genes in the tumor cells, especially the process mediated by RNA‐binding protein (RBP) remains unclear. SAMD4A is a conserved RBP across fly to mammals, and is believed to play an important role in controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(78 reference statements)
2
15
0
Order By: Relevance
“…In particular, SAMD4A , which is a conserved RBP across mammals that controls gene translation and stability, has been recently reported as a BC suppressor. Specifically, it destabilizes the expression of proangiogenic transcripts by physically interacting with the stem loop structure in their 3′UTR through its sterile alpha motif (SAM) domain [ 57 ]. Moreover, we show here that SAMD4A is negatively correlated (r = −0.44, p < 0.0001) with ERα mRNA levels in ERα+ BCs, and accordingly, it was reported to be repressed in BC tissues and cancer cell lines where its low expression is associated with the poor survival of patients and its overexpression inhibited tumor angiogenesis and cancer progression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, SAMD4A , which is a conserved RBP across mammals that controls gene translation and stability, has been recently reported as a BC suppressor. Specifically, it destabilizes the expression of proangiogenic transcripts by physically interacting with the stem loop structure in their 3′UTR through its sterile alpha motif (SAM) domain [ 57 ]. Moreover, we show here that SAMD4A is negatively correlated (r = −0.44, p < 0.0001) with ERα mRNA levels in ERα+ BCs, and accordingly, it was reported to be repressed in BC tissues and cancer cell lines where its low expression is associated with the poor survival of patients and its overexpression inhibited tumor angiogenesis and cancer progression [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it destabilizes the expression of proangiogenic transcripts by physically interacting with the stem loop structure in their 3′UTR through its sterile alpha motif (SAM) domain [ 57 ]. Moreover, we show here that SAMD4A is negatively correlated (r = −0.44, p < 0.0001) with ERα mRNA levels in ERα+ BCs, and accordingly, it was reported to be repressed in BC tissues and cancer cell lines where its low expression is associated with the poor survival of patients and its overexpression inhibited tumor angiogenesis and cancer progression [ 57 ]. Another EMT regulator RBP, QKI , is repressed by apoERα and negatively correlated (r = −0.37; p < 0.0001) with ERα mRNA levels in Erα+ BCs, as previously reported [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, SAMD4A is a conserved RBP found in a variety of species, and it regulates gene translation and stability. SAMD4A has been linked to angiogenesis and tumor progression in breast cancer, and its low expression in human breast tumor tissues/cells has been linked to a poor prognosis and survival [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NADH oxidase ENOX1 targets tumour vasculature and can be used in tumour treatment (58,59). Coincidentally, Zhou et al (60) also reported SAMD4A as a novel breast tumour angiogenesis suppressor in breast cancer. ZC3H10 regulates lipid metabolism and may also offer novel routes toward treatments for obesity (61).…”
Section: Discussionmentioning
confidence: 99%